A practical approach to deloading: Recommendations and considerations for strength and physique sports - Bell, L.; Darragh, I. A. J.; Travis, S. K.; Rogerson, D.; Nolan, D. (Strength and Conditioning Journal, 2025)
Deloading is a period of reduced training stress where training demand is intentionally reduced to mitigate physiological and psychological fatigue and promote recovery. A deload is commonly implemented to enhance readiness for subsequent training and occurs between or during training phases. During a deload, training is typically modified by reducing the intensity of effort, training volume, duration, or frequency. Adjustments in exercise selection are based on recovery goals and the specific demands of the athlete's training. Deloads are commonly preplanned and implemented into the training program every 4-8 weeks based on the structure of the training cycle and recovery needs. Alternatively, deloads are sometimes applied reactively using an autoregulatory approach to accommodate unexpected fatigue or performance decrements. While deloading shares conceptual similarities with tapering and training cessation, it should be differentiated based on its objective, structure, and positionality with the overall training program. The purpose of this article is to describe the current research landscape, propose areas for future research, and to provide broad practical recommendations for implementing deloading within the strength and physique sports training program.